Projetos desenvolvimentistas na Amazônia e a resistência dos Waimiri-Atroari (1964-2014) - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This thesis aims to analyze the resistance process Waimiri-Atroari people cope with the impacts of major development projects in the Amazon. The defense of its territory traditionally occupied since time immemorial, is the guiding element of this study. We take as temporal cut the last fifty years of his Ethnohistory, having as a backdrop, the "(un) commemoration" of the 1964 civil-military coup until mid-2014, when this cycle is evidenced by the publication of the Final Report the National Truth Commission. Throughout the work, dialogue with anthropology is also present in an attempt to understand their different practices of resistance.
Keywords: Etno-história; Povo Waimiri-Atroari; Projetos de Desenvolvimento; Práticas de Resistência; Ethnohistory; Waimiri-Atroari people; Development projects; Practices of resistence; CIÊNCIAS HUMANAS: HISTÓRIA